An Entropy Proof of the Arithmetic Mean–Geometric Mean Inequality. Issue 6 (2nd July 2020) - Graham, Cole; Tokieda, Tadashi
Abstract: Many proofs are known for the inequality between the arithmetic mean and the geometric mean. This note gives a new derivation, interpreting the means as final and initial values of entropy, and the inequality as the second law of thermodynamics.